Ocean biogeochemical models as management tools: a case study for Atlantic wolffish and declining oxygen. (27th November 2015) - Bianucci, Laura; Fennel, Katja; Chabot, Denis; Shackell, Nancy; Lavoie, Diane
Abstract: Society is moving towards a no-analogue climate that will fundamentally affect ocean ecosystems and the socio-economic activities that depend on them. Warming has led to displacements of various populations, calling for an adaptation of fisheries management plans and Species at Risk recovery strategies. Dissolved oxygen (DO) has declined, but its impacts on habitat are much less studied. Severe hypoxia is lethal, but even sublethal hypoxia can trigger species displacements. We use Atlantic wolffish ( Anarhichas lupus ) as a case study to investigate the impact of DO on optimal habitat on the Scotian Shelf, Canada, considering that their habitat becomes suboptimal at DO lower than ∼65% saturation. First, we demonstrate that DO has decreased using two observational climatologies before and after 1980, and that the spatial pattern of the associated expansion of low oxygen waters (DO < ∼65% saturation) over the shelf is consistent with the observed contraction of Wolffish population. Then, we use a spatially explicit regional ocean model that couples physical and biological processes to simulate a scenario in which a continued decline of DO in the open ocean leads to a further expansion of low oxygen waters over the shelf. The future low DO extends to regions that currently have high Wolffish biomass, and likely other species as well. While fishing pressure likely drives the observed decline in Wolffish, both observations and model scenario suggest that DO can further constrain habitat. We argue that management/recovery plans should consider DO as one of the potential stressors of not just Atlantic wolffish but any oxygen-sensitive species. Finally, we emphasize that biogeochemical ocean models can inform management by elucidating the direction and ranges of future changes in ocean environmental conditions.